Distinct Roles of Ascorbic Acid in Extracellular Vesicles and Free Form: Implications for Metabolism and Oxidative Stress in Presymptomatic Huntington S Disease: Ascorbic Acid in Early Huntington S Disease - Rojas-Montecinos, P; Lara-Suzarte, M (Elsevier Inc., 2025)
Huntington s disease (HD) is a neurodegenerative disorder caused by a CAG trinucleotide repeat expansion in the first exon of the huntingtin gene. The huntingtin protein (Htt) is ubiquitously expressed and localized in several organelles, including endosomes, where it plays an essential role in intracellular trafficking. Presymptomatic HD is associated with a failure in energy metabolism and oxidative stress. Ascorbic acid is a potent antioxidant that plays a key role in modulating neuronal metabolism and is highly concentrated in the brain. During synaptic activity, neurons take up ascorbic acid released by glial cells; however, this process is disrupted in HD. In this study, we aim to elucidate the molecular and cellular mechanisms underlying this dysfunction. Using an electrophysiological approach in presymptomatic YAC128 HD slices, we observed decreased ascorbic acid flux from astrocytes to neurons, which altered neuronal metabolic substrate preferences. Ascorbic acid efflux and recycling were also decreased in cultured astrocytes from YAC128 HD mice. We confirmed our findings using GFAP-HD160Q, an HD mice model expressing mutant N-terminal Htt mainly in astrocytes. For the first time, we demonstrated that ascorbic acid is released from astrocytes via extracellular vesicles (EVs). Decreased number of particles and exosomal markers were observed in EV fractions from cultured YAC128 HD astrocytes and Htt-KD cells. We observed reduced number of multivesicular bodies (MVBs) in YAC128 HD striatum via electron microscopy, suggesting mutant Htt alters MVB biogenesis. EVs containing ascorbic acid effectively reduced reactive oxygen species, whereas “free” ascorbic acid played a role in modulating neuronal metabolic substrate preferences. These findings suggest that the early redox imbalance observed in HD arises from a reduced release of ascorbic acid-containing EVs by astrocytes. Meanwhile, a decrease in “free” ascorbic acid likely contributes to presymptomatic metabolic impairment. © 2024 The Authors